ANALISIS DAYA DUKUNG TANAH DASAR BERDASARKAN UJI CBR LABORATORIUM DAN UJI CBR LAPANGAN PADA RUAS JALAN KAMPUS UNIPAS MOROTAI - Fitro Darwis; Elfira Resti Mulya (Fakultas Teknik Universitas Khairun, 2022)
The development of land transportation, in this case the highway in Morotai Island Regency, is currently very fast. One of the roads planned for the construction of a new road is the Unipas Morotai Campus Road Section. So far, the construction of new roads in Morotai Island Regency has not been optimally carried out by a survey to test the condition of the subgrade and the strength of the base soil. The purpose of this study was to determine the carrying capacity of the subgrade for the purpose of planning pavement thickness on the Unipas Morotai campus road through direct field testing with laboratory testing. The results showed that the soil types in the 3 sampling locations were loamy soils with high water content in the field between 30-35%. The laboratory CBR value at point 01 is 33%, point 2 is 28% and point 3 is 49%. These results indicate that from the results of laboratory testing, subgrade fulfills the requirements as a subgrade on road pavement where CBR> 5%. The CBR value of the field tested at point 6 test points gave a varied value of 4.64% -6.96%. These results indicate that from the lab test results, subgrade fulfills the requirements as a subgrade on the pavement where CBR> 5% at point 01 , and point 04. Meanwhile, the other 4 points did not meet their CBR values so that special compaction was needed in the field..